Identification and functional characterization of ORF19.5274, a novel gene involved in both azoles susceptibility and hypha development in Candida albicans - Huang, Mingjiao; Yang, Longbing; Zhou, Luoxiong; Sun, Chaoqin; Zhao, Wenjing; Peng, Jian; Jiao, Zhenlong; Tian, Chunren; Guo, Guo (Frontiers in Microbiology, 2022)
Azole resistance is becoming increasingly serious due to the frequent recurrence of fungal infections and the need for long-term clinical prevention. In our previous study, we discovered ORF19.5274 with an unknown function by TMT™ quantitative proteomics technology after fluconazole (FLC) treatment of Candida albicans. In this study, we created the target gene deletion strain using CRISPR-Cas9 editing technology to see if ORF19.5274 regulates azole sensitivity. The data showed that ORF19.5274 was involved in hyphal development and susceptibility to antifungal azoles. Deleting this gene resulted in defective hyphal growth in solid medium, while only a weak lag in the initiation of hyphal development and restoring hyphal growth during the hyphal maintenance phase under liquid conditions. Moreover, intracellular reactive oxygen species (ROS) assay and propidium iodide staining assays showed increased endogenous ROS levels and membrane permeability, but decreased metabolic activity of biofilm in orf19.5274Δ/Δ after treatment with FLC in comparison with either SC5314 or orf19.5274Δ/Δ::ORF19.5274 strains. More importantly, orf19.5274Δ/Δ significantly enhanced the FLC efficacy against C. albicans in infected Galleria mellonella larvae. The above characteristics were fully or partially restored in the complemented strain indicating that the changes caused by ORF19.5274 deletion were specific. In summary, the ORF19.5274 gene is required for hyphal development of C. albicans, and is correlated with the response to antifungal azoles in vitro and in vivo. The identification of ORF19.5275 is promising to expand the potential candidate targets for azoles.